Pengembangan Media Pembelajaran Teachmint pada Mata Pelajaran Korespondensi Kelas X Manajemen Perkantoran di SMK Tunas Pembangunan - Suci Dian Permatasari; Roni Faslah; Darma Rika Swaramarinda (Syntax Corporation Indonesia, 2024)
This research aims to: (1) develop Teachmint learning media in the subject of Correspondence, (2) to obtain feasibility information from Teachmint learning media in the subject of Correspondence class X of Office Management at SMK Tunas Pembangunan. The type of research used is research and development (RnD) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development method. This research took place at SMK Tunas Pembangunan which was carried out from May 2024 to July 2024. The data collection technique was collected by interviews with teachers of SMK Tunas Pembangunan. The feasibility of learning media is assessed by media experts and material experts. Data analysis was carried out by qualitative and quantitative analysis. Based on the research that has been carried out, Teachmint learning media on the subject of Correspondence has been developed. The results of expert validation are known that Teachmint learning media in the subject of Correspondence class X Office Management at SMK Tunas Pembangunan is very feasible to use with an average validation score of 86.3% for media experts with the category of